Current Role of Surgery in Pancreatic Cancer With Synchronous Liver Metastasis. (23rd November 2020) - Zhou, Wentao; Wang, Dansong; Lou, Wenhui
Pancreatic cancer with synchronous liver metastasis has an extremely poor prognosis, and surgery is not recommended for such patients by the current guidelines. However, an increasing body of studies have shown that concurrent resection of pancreatic cancer and liver metastasis is not only technically feasible but also beneficial to the survival in the selected patients. In this review, we aim to summarize the short- and long-term outcomes following synchronous liver metastasectomy for pancreatic cancer patients, and discuss the potential criteria in selecting appropriate surgical candidates, which might be helpful in clinical decision-making.